Towards a Thread-Local Proof Technique for Starvation Freedom - Schellhorn, Gerhard; Travkin, Oleg; Wehrheim, Heike (Integrated Formal Methods - 12th International Conference, IFM 2016, Reykjavik, Iceland, June 1-5, 2016, Proceedings)

Proving Opacity of a Pessimistic STM - Doherty, Simon; Dongol, Brijesh; Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (20th International Conference on Principles of Distributed Systems, OPODIS 2016, December 13-16, 2016, Madrid, Spain)

Deriving approximation tolerance constraints from verification runs - Isenberg, Tobias; Jakobs, Marie{-}Christine; Pauck, Felix; Wehrheim, Heike (CoRR)

Can the Crowd Substitute Experts in Evaluation of Creative Ideas? An Experimental Study Using Business Models - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 22nd Americas' Conference on Information Systems (AMCIS))

Can the Crowd Substitute Experts in Evaluation of Creative Jobs? The Case of Business Models - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Read this Paper! A Field Experiment on the Role of a Call-To-Action in Paid Search - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Fitness and fatness in relation with attention capacity in European adolescents: The HELENA study - Cadenas-Sanchez, Cristina; Vanhelst, Jeremy; Ruiz, Jonatan R.; Castillo-Gualda, Ruth; Libuda, Lars; Labayen, Idoia; De Miguel-Etayo, Pilar; Marcos, Ascensión; Molnár, Eszter; Catena, Andrés; Moreno, Luis A.; Sjöström, Michael; et al. (Journal of Science and Medicine in Sport)

Sedentary Behavior Is Independently Related to Fat Mass among Children and Adolescents in South China - Xue, Hongmei; Tian, Guo; Duan, Ruonan; Quan, Liming; Zhao, Li; Yang, Min; Libuda, Lars; Muckelbauer, Rebecca; Cheng, Guo (Nutrients)

Lunch at school and children’s cognitive functioning in the early afternoon: results from the Cognition Intervention Study Dortmund Continued (CoCo) - Schröder, Maike; Müller, Katrin; Falkenstein, Michael; Stehle, Peter; Kersting, Mathilde; Libuda, Lars (British Journal of Nutrition)
Abstract Studies about effects of school lunch on children’s cognition are rare; two previous studies (CogniDo, CogniDo PLUS) generally found no negative effects of lunch on children’s cognitive performance at the end of lunch break (i.e. 45 min after finishing lunch), but suggested potential beneficial effects for single parameters. Therefore, the present study investigated the hypothesis of potential positive effects of school lunch on cognitive performance at early afternoon (90 min after finishing lunch). A randomised, cross-over intervention trial was conducted at a comprehensive school with fifth and sixth grade students. Participants were randomised into two groups: On day 1, group 1 did not eat lunch, whereas group 2 received lunch ad libitum . On day 2 (1 week later), group 2 did not eat lunch and group 1 received lunch ad libitum . The cognitive parameters task switching, working memory updating and alertness were tested using a computerised test battery 90 min after finishing the meal. Of the 204 recruited children, fifty were excluded because of deviations from the study protocol or absence on one of the 2 test days, which resulted in 154 participants. Data showed no significant effects of lunch on task switching, working memory updating and alertness ( P values between 0·07 and 0·79). The present study suggests that school lunch does not seem to have beneficial effects on children’s cognitive functions regarding the conducted tests at early afternoon. Together with our previous studies, we conclude that school lunch in general has no negative effects on cognitive performance in children. However, beneficial effects seem to be restricted to a relatively short time period after eating lunch.

Changes in water and sugar-containing beverage consumption and body weight outcomes in children - Muckelbauer, Rebecca; Gortmaker, Steven L.; Libuda, Lars; Kersting, Mathilde; Clausen, Kerstin; Adelberger, Bettina; Müller-Nordhorn, Jacqueline (British Journal of Nutrition)
Abstract An intervention study showed that promoting water consumption in schoolchildren prevented overweight, but a mechanism linking water consumption to overweight was not substantiated. We investigated whether increased water consumption replaced sugar-containing beverages and whether changes in water or sugar-containing beverages influenced body weight outcomes. In a secondary analysis of the intervention study in Germany, we analysed combined longitudinal data from the intervention and control groups. Body weight and height were measured and beverage consumption was self-reported by a 24-h recall questionnaire at the beginning and end of the school year 2006/2007. The effect of a change in water consumption on change in sugar-containing beverage (soft drinks and juices) consumption, change in BMI (kg/m 2 ) and prevalence of overweight and obesity at follow-up was analysed using regression analyses. Of 3220 enroled children, 1987 children (mean age 8·3 ( sd 0·7) years) from thirty-two schools were analysed. Increased water consumption by 1 glass/d was associated with a reduced consumption of sugar-containing beverages by 0·12 glasses/d (95 % CI −0·16, −0·08) but was not associated with changes in BMI ( P =0·63). Increased consumption of sugar-containing beverages by 1 glass/d was associated with an increased BMI by 0·02 (95 % CI 0·00, 0·03) kg/m 2 and increased prevalence of obesity (OR 1·22; 95 % CI 1·04, 1·44) but not with overweight ( P =0·83). In conclusion, an increase in water consumption can replace sugar-containing beverages. As sugar-containing beverages were associated with weight gain, this replacement might explain the prevention of obesity through the promotion of water consumption.